2017
DOI: 10.1155/2017/4671305
|View full text |Cite
|
Sign up to set email alerts
|

Applying Sutureless Encircling Number 41 Band and Transscleral Chandelier-Assisted Laser Retinopexy for Scleral Buckling Procedure

Abstract: Purpose To assess the outcome of sutureless encirlcing number 41 band and transscleral laser retinopexy in uncomplicated rhegmatogenous retinal detachment (RRD), using a wide-angle viewing system (WAVS) and chandelier endoillumination. Methods Prospective intervention study included 30 eyes of 30 patients presenting with RRD of recent onset indicated for SB. All cases were treated by sutureless encircling number 41 band and transscleral laser retinopexy. Visualization was provided by the Resight WAVS and a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Some studies excluded the gauge size as a risk factor for the vitreous prolapse, 22 while others believed it might be a contributing factor. 13,26,29 In our study, we had 52.1% incidence of vitreous entrapment (P2) on UBM, where other studies reported lower rates. 28 Vitreous incarceration plugging the sclerotomy can lead to many complications.…”
Section: Vitreous Prolapse and Entrapmentmentioning
confidence: 45%
See 1 more Smart Citation
“…Some studies excluded the gauge size as a risk factor for the vitreous prolapse, 22 while others believed it might be a contributing factor. 13,26,29 In our study, we had 52.1% incidence of vitreous entrapment (P2) on UBM, where other studies reported lower rates. 28 Vitreous incarceration plugging the sclerotomy can lead to many complications.…”
Section: Vitreous Prolapse and Entrapmentmentioning
confidence: 45%
“…Some studies excluded the gauge size as a risk factor for the vitreous prolapse, 22 while others believed it might be a contributing factor. 13,26,29…”
Section: Discussionmentioning
confidence: 99%
“…2,8,18,24 Six studies reported this complication, with incidences ranging from 5% to 48%. 2,8,10,18,24,30 Sutures at the sclerotomy site were also needed in some of the reported cases. 10,30 Authors have proposed methods to reduce the risk for vitreous prolapse, including using valved cannulas, paracentesis, or subretinal fluid drainage to lower IOP before trocar removal; inserting the trocar obliquely; or plugging the cannula during episcleral procedures as well during removal of the trocar.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that fixing the silicone band to the sclera before trocar and cannula insertion allows better control of the endoilluminator and minimizes the risk for lens touch and creation of new retinal breaks. 18 In pseudophakic patients, PPV is performed more often than standard scleral buckling. 8 Factors such as poor pupil dilation, cortical remnants, capsule opacification, and intraocular lens optical aberrations in pseudophakic patients make it difficult to obtain a satisfactory view with the indirect ophthalmoscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation